2015
DOI: 10.1002/pola.27564
|View full text |Cite
|
Sign up to set email alerts
|

Low band-gap diketopyrrolopyrrole-containing polymers for near infrared electrochromic and photovoltaic applications

Abstract: Donor-acceptor type polymers bearing diketopyrrolopyrrole and 3,4-ethylenedioxythiophene units are reported. The polymers are green and exhibit very low band-gaps (1.19 eV) with strong and broad absorption (maxima of about 830 nm) in the near infrared (NIR) region in their neutral film states. The polymers display color changes between dark green and light blue with exceptional optical contrasts in the NIR regions of up to 78 and 63% as thin films and single-layer electrochromic devices, respectively. Fast swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 59 publications
2
20
1
Order By: Relevance
“…The thin films of all the polymers showed quasi-reversible oxidation and reduction waves with the onset oxidation potentials (E ox ) at around 0.4~0.6 V (vs Ag/AgCl) and onset reduction potentials (E red ) at around -1.1 V. The oxidation behavior was similar to the reported DPP-based polymers [15]. The E ox values suggested that the triphenylamine derivatives are stronger donors than the fluorene unit and that the substitution of the methoxy group at the para-position with respect to the nitrogen atom facilitated the oxidation, whereas the cyano group substitution made it more difficult.…”
Section: Optical and Electrochemical Propertiessupporting
confidence: 58%
See 2 more Smart Citations
“…The thin films of all the polymers showed quasi-reversible oxidation and reduction waves with the onset oxidation potentials (E ox ) at around 0.4~0.6 V (vs Ag/AgCl) and onset reduction potentials (E red ) at around -1.1 V. The oxidation behavior was similar to the reported DPP-based polymers [15]. The E ox values suggested that the triphenylamine derivatives are stronger donors than the fluorene unit and that the substitution of the methoxy group at the para-position with respect to the nitrogen atom facilitated the oxidation, whereas the cyano group substitution made it more difficult.…”
Section: Optical and Electrochemical Propertiessupporting
confidence: 58%
“…The excellent reversibility was previously reported for the anodic electrochromism of the DPP-thiophene copolymers [13][14][15][16][17][18]. Unfortunately, the DPPbased polymers with the fluorene or triphenylamine donors in this study did not show such a reversible electrochromism in the anodic direction.…”
Section: Switching Timecontrasting
confidence: 43%
See 1 more Smart Citation
“…[3][4][5][6] To date, blue-, green-, magenta-, redcolored and black EC polymers have been reported. [7][8][9][10] In addition, conjugated polymers that are able to switch reversibly between colored and transparent states in both visible and nearinfrared (NIR) regions by electrochemical means are reported.…”
Section: Introductionmentioning
confidence: 99%
“…Thermogravimetric analysis (TGA) was conducted on a PerkinElmer Pyris Diamond TG instrument from 20 to 800 C at a heating rate of 10 Synthesis of monomers and polymers The solution was degassed with argon for 40 min. Then Pd 2 (dba) 3 (8 mg) and P(o-tol) 3 (30 mg) were added to the solution, followed by degassing and charging with argon several times. The reaction mixture was stirred at 100 C for 72 h. Aer cooling down to 70 C, 10 mL of aqueous solution of sodium diethyldithiocarbamate trihydrate was added to the mixture and the mixture was stirred for 12 hours to remove the residual catalyst.…”
mentioning
confidence: 99%